Student Mental Health in California's K-12 Schools School Principal Reports of Common Problems and Activities to Address Them - Kaufman, Julia H. (RAND Corporation, 2015)
Reports results of a survey of K-12 principals to take inventory of student mental health and wellness needs and the types of programs schools are most often implementing to help students in California's public schools.